PRINCIPLES OF THE CIRCULAR ECONOMY WITHIN THE STRATEGIES AND BUSINESS MODELS OF MULTINATIONAL ENTERPRISES - DOBRE-BARON OANA; NIȚESCU ALINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The circular economy marks a significant evolution in the global approach to production, consumption, and waste management. Furthermore, its core principles have become increasingly critical as their implementation has increased by leading actors of the transition to the green economy, and especially within business activities. This study provides researchers and practitioners a qualitative analysis of the new circular economy principles adopted by companies, and in particular by multinational corporations, also included in their strategies and business models.